Effects of Different Pretreatment Oat Flour on the Quality of Extruded Instant Rice - Junling WU; Huihui LIU; Weiguo WU; Xianlong REN; Wenhui YAN; Luyan LIAO (Shipin gongye ke-ji)
To improve the dietary fiber content of extruded instant rice and the application value of oats in extruded instant rice, 6 kinds of pretreatment (high pressure steaming, atmospheric pressure steaming, stir-frying, germination, cellulase enzyme digestion, α-amylase enzyme digestion) were investigated in the mixture of oat flour and broken rice, using the mixture of unpretreated oat flour and broken rice flour (oats:broken rice=1:4) as a control, to investigate the pasting characteristics, degree of pasting, water and water characteristics, and the mixture of six kinds of pretreatment in the mixture of oat flour and broken rice. The comprehensive quality (rehydration, sensory quality, textural quality) characteristics and dietary fiber content of the extruded instant rice were prepared to analyze the correlation between the raw material characteristics and the quality of the extruded instant rice, and to screen out the most suitable oat pretreatment method for processing high dietary fiber extruded instant rice. Results showed that the dietary fiber content of extruded instant rice with the addition of atmospheric pressure steamed oat flour was the highest (7.91%). The germinated oat flour had a significant effect on the pasting characteristics of the raw material mixtures (P<0.05), which was the most obvious compared with the other pretreatments. The water solubility index (WSI) of the germinated oat flour added before extrusion was the highest (4.16%) (P<0.05), while that of the extruded instant rice with the addition of fried oat flour was the highest (P<0.05). The highest WSI (5.75%) was obtained with the addition of fried oat flour after extrusion. The addition of fried oat flour had the highest odor and taste scores, and the addition of atmospheric steaming oats had the best sensory and composite scores. The peak viscosity and grain value viscosity of the raw material mixes were significantly negatively correlated with the hardness, gelatinous viscosity, and composite scores of their instant rice (P<0.05), and significantly positively correlated with the sensory scores (P<0.05). Therefore, atmospheric pressure steaming could be used as a pretreatment of oats for the preparation of high dietary fiber oat-broken rice extruded instant rice with the best composite quality.